Zebra pattern in rocks as a function of grain growth affected by second-phase particles - Kelka, Ulrich; Koehn, Daniel; Beaudoin, Nicolas (Frontiers in Physics, 2015)
In this communication we present a simple microdynamic model which can explain the beginning of the zebra pattern formation in rocks. The two dimensional model consists of two main processes, mineral replacement along a reaction front, and grain boundary migration affected by impurities. In the numerical model we assume that an initial distribution of second-phase particles is present due to sedimentary layering. The reaction front percolates the model and redistributes second-phase particles by shifting them until the front is saturated and drops the particles again. This produces and enhances initial layering. Grain growth is hindered in layers with high second-phase particle concentrations whereas layers with low concentrations coarsen. Due to the grain growth activity in layers with low second-phase particle concentrations these impurities are collected at grain boundaries and the crystals become very clean. Therefore the white layers in the pattern contain large grains with low concentration of second-phase particles, whereas the dark layers contain small grains with a large second-phase particle concentration.